Analisis AHP TOPSIS dalam Pemilihan Teknologi Pengolahan Sampah Berbasis Keadilan Energi - Miza Zuda Nurlael; Rudy Hartanto; Wing Wahyu Winarno; Irfan Budi Santoso (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2024)
The amount of waste in Bantul Regency increased by 4.96% from 2020 to 2021, indicating that the capacity of final disposal sites (FDS) in Piyungan District, Bantul Regency, was decreasing. The peak occurred from 23 July 2023 to 5 September 2023, during which the Piyungan FDS could not provide waste disposal services. The high poverty rate in Bantul Regency forces the government to process waste into energy as a sustainable waste management effort. However, numerous criteria make it difficult to determine which technology is most suitable for this purpose. Energy justice criteria need to be considered when choosing technology and efforts to improve the welfare of Bantul Regency's residents. This research aimed to present an assessment of each alternative technology for processing waste into energy and decide one suitable alternative for sustainable waste management in Bantul Regency using a combination of AHP and TOPSIS methods based on energy justice. AHP was used to assess the level of importance of each criterion, while TOPSIS was used to determine the optimal alternative based on the criteria by considering costs and benefits. The findings showed that the preference value for three alternatives was 0.579, 0.414, and 0.341 for incineration, pyrolysis, and gasification, respectively. According to these preference value, incineration was identified as the foremost viable alternative technology for implementation in Bantul Regency. Gasification and pyrolysis ranked as the subsequent and third alternatives, respectively.